Systematic re-evaluation of genes from candidate gene association studies in migraine using a large genome-wide association data set. (June 2016) - de Vries, Boukje; Anttila, Verneri; Freilinger, Tobias; Wessman, Maija; Kaunisto, Mari A; Kallela, Mikko; Artto, Ville; Vijfhuizen, Lisanne S; Göbel, Hartmut; Dichgans, Martin; Kubisch, Christian; Ferrari, Michel D; et al.
Background: Before the genome-wide association (GWA) era, many hypothesis-driven candidate gene association studies were performed that tested whether DNA variants in genes that had been selected based on prior knowledge about migraine pathophysiology were associated with migraine. Most studies involved small sample sets without robust replication, thereby making the risk of false-positive findings high. Genome-wide marker data of thousands of migraine patients and controls from the International Headache Genetics Consortium provide a unique opportunity to re-evaluate key findings from candidate gene association studies (and other non-GWA genetic studies) in a much larger data set. Methods: We selected 21 genes from published candidate gene association studies and six additional genes from other non-GWA genetic studies in migraine. Single nucleotide polymorphisms (SNPs) in these genes, as well as in the regions 500 kb up- and downstream, were inspected in IHGC GWAS data from 5175 clinic-based migraine patients with and without aura and 13, 972 controls. Results: None of the SNPs in or near the 27 genes, including the SNPs that were previously found to be associated with migraine, reached the Bonferroni-corrected significance threshold; neither when analyzing all migraine patients together, nor when analyzing the migraine with and without aura patients or males and females separately. Conclusion: The available migraine GWAS data provide no clear evidence for involvement of the previously reported most promising candidate genes in migraine.